Determination of Factors Influencing Condom Usage among Male to Female Transgender in Chennai City - M. Sudha; L. S. Suga Priyanka (Issues and Development in Health Research Vol. 7, 2021)
Economic insecurity, lack of career possibilities, social rejection, and gender-based violence and abuse are all issues that male to female transgender people face. As a result, they are at risk of becoming one of the groups afflicted by the HIV epidemic. Due to lack of education and employment, they are forced to engage in sex work, with research indicating that 90% of Male to Female Transgender in India engage in sex work, making them exposed to HIV infection. This necessitated a thorough examination of condom usage patterns as well as the factors that influence condom use. Objectives: Study the condom usage patter among the respondents and also the various factors that determine their condom usage. Methodology: In June 2016, 784 Male to Female Transgender enrolled in the CBO - Thozhi, 275 in Transgender Rights Association (TRA) and 282 in Tamil Nadu Aravanigal Association (THAA). A total of 299 people were included in the study. In depth interviews (9) and three focus group discussions (6 respondents in each group) were done as part of a mixed method study to obtain qualitative data. Finding: One fourth (25%) of the respondents lived alone, while nearly one-fifth (18%) of the respondents lived with their male sex partners. Sex work was the primary occupation of more than a quarter (28%) of those surveyed, while it was the secondary occupation of a third (34%) of those surveyed. Only 40% of the 120 people who worked in the sex industry used condoms on a regular basis, and only 40% of the 134 people who had permanent male partners used condoms on a regular basis. Need for more money (69 percent), alcohol influence (63 percent), refusal to use by law enforcement and anti-socialists (24 percent), for sexual pleasure (74 percent), and with attractive clients (54 percent). For respondents who had permanent partners, love/scared of getting disserted/inability to use with husband was some of the responses expressed by the respondents.